On the Use of Galaxy Catalogs in Gravitational-wave Parameter Estimation - Geoffrey Mo; Carl-Johan Haster; Erik Katsavounidis (The Astrophysical Journal)
A major challenge in gravitational-wave (GW) multimessenger astrophysics is the imprecise localization of GW compact binary mergers. We investigate the use of a method to include galaxy catalog information in performing parameter estimation of these events. We test its effectiveness with the GW events GW170817, GW190425, and GW190814, as well as with simulated binary neutron star mergers. For GW170817, we recover the true host galaxy as the most probable galaxy after a straightforward mass reweighting, with significantly decreased localization area and volume. On the simulated sample, however, we do not find improvement compared to performing a simple galaxy catalog crossmatch with a regular GW localization. Future investigations into sampling methods may yield improvements that increase the viability of this method.